Syntheses of Carbazoles by Photosensitized Electrocyclization of Triarylamines. Effect of Inductive Electron‐Withdrawing Groups on the Photocyclization - Romero Cordero, Ivan Exehomio (2025)
The acetone-sensitized [6π]-electrocyclization of unsubstituted, mono-, and disubstituted triarylamines (TAAs: substituents H, CH₃, CH₃O, Cl, CnF₂n+1; n=1, 3, 4, 6, 8, 10) under 310 nm light led to the formation of endo- and exo-carbazoles in high yields; particularly, TAAs substituted with inductive electron-withdrawing groups (Cl, CnF2n+1) exhibit remarkable endo-selectivity towards cyclization. For TAAs substituted with both inductive electron- withdrawing and donating groups, the photocyclization towards endo carbazoles is dictated by the presence of the electron-withdrawing groups. Chemical yields (%), quantum yields of conversion (φR), apparent cyclization rate constants (kcyc), and Hammett plots correlations are illustrated for all substituted TAAs in acetone. Photophysical studies reveal that TAAs substituted with resonance electron-withdrawing groups (OAc, NO2, CHO) do not undergo electrocyclization in acetone at 310 nm due to formation of charge-transfer states that vastly deactivate the triplet reactive manifold, paralleling the behavior observed in MeCN as solvent. Absorption and emission spectra, Stokes shifts, and singlet excited state energies are illustrated for substituted TAAs and carbazoles. In-silico studies support the high stereoselectivity observed for the preferred endo- photosensitized [6π]-electrocyclization of Cl- and perfluoroalkyl-substituted TAAs.